Optimalisasi Sanitasi Pasar Sesuai Standar Pasar Sehat - Melisa Maulani; Rina Noor Hayati; Iitra Achbar Sahdian; Ulul Azmiyah Sudarmo (Buletin Keslingmas, 2026)
Traditional markets serve as central hubs of community economic activity and play a vital role in meeting daily basic needs. However, the high intensity of interactions within these markets may increase the risk of disease transmission, particularly when environmental sanitation is inadequately managed. This study aims to analyze the current condition of sanitation facilities at Sanggam Adji Dilayas Market, Berau Regency, and to formulate recommendations for improvement toward achieving a healthy market in accordance with the provisions of the Indonesian Ministry of Health Regulation No. 17 of 2020. The research employed a descriptive analysis with a rationalistic approach. Recommendations were formulated using a triangulation method, involving direct observation and interviews based on six key sanitation indicators: provision of clean water, toilet facilities, waste management, drainage systems, handwashing facilities, and vector control. The findings reveal that the market has not yet met the criteria for a healthy market, with a feasibility score of 62%. The main issues identified include insufficient toilet facilities, damaged wastewater (black water) channels, suboptimal waste management systems, clogged drainage, the absence of a wastewater treatment plant (WWTP), and the lack of handwashing facilities and vector control measures in strategic areas. Based on these results, eleven recommendations were proposed to enhance sanitation facilities, encompassing infrastructure improvements, waste separation and treatment, provision of a WWTP, and education on hygienic behavior. These improvements are expected to support the implementation of healthy market standards, enhance the comfort of both vendors and visitors, and contribute to the sustainable realization of a Healthy City in Berau Regency.